Genotypic variations in field isolates of Theileria species infecting giraffes (Giraffa camelopardalis tippelskirchi and Giraffa camelopardalis reticulata) in Kenya - Githaka, Naftaly W.; Konnai, S.; Skilton, Robert A.; Kariuki, E.; Kanduma, Esther G.; Murata, S.; Ohashi, K. (Elsevier, 2013)
Recently, mortalities among giraffes, attributed to infection with unique species of piroplasms were reported in South Africa. Although haemoparasites are known to occur in giraffes of Kenya, the prevalence, genetic diversity and pathogenicity of these parasites has not been investigated. In this study, blood samples from 13 giraffes in Kenya were investigated microscopically and genomic DNA extracted. PCR amplicons of the hyper-variable region 4 (V4) of Theileria spp. small subunit ribosomal RNA (18S rRNA) gene were hybridized to a panel of genus- and species-specific oligonucleotide probes by reverse line blot (RLB). Two newly designed oligonucleotide probes specific for previously identified Theileria spp. of giraffes found single infections in eight of the specimens and mixed infections in the remaining five samples. Partial 18S rRNA genes were successfully amplified from 9 samples and the PCR amplicons were cloned. A total of 28 plasmid clones representing the Kenyan isolates were analyzed in the present study and compared with those of closely-related organisms retrieved from GenBank. In agreement with RLB results, the nucleotide sequence alignment indicated the presence of mixed infections in the giraffes. In addition, sequence alignment with the obtained 18S rRNA gene sequences revealed extensive microheterogeneities within and between isolates, characterized by indels in the V4 regions and point mutations outside this region. Phylogeny with 18S rRNA gene sequences from the detected parasites and those of related organisms places Theileria of giraffes into two major groups, within which are numerous clades that include the isolates reported in South Africa. Collectively, these data suggest the existence of at least two distinct Theileria species among giraffes, and extensive genetic diversity within the two parasite groups.